2015
DOI: 10.1007/s00217-015-2513-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of sunstruck flavor-related substances in malted barley, triticale and spelt

Abstract: had a negative influence on the content of cysteine, methionine and tryptophan of triticale. The germination time and temperature showed a negative influence on the tryptophan content of spelt. With the knowledge gained, the potential of different cereals for its use in the development of malted cereal-based beverages can be determined. Moreover, the influence of malting process on the content of these substances as well as differences between the raw materials was defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…With variations of parameters during the process of malting, such as degree of steeping, and time and temperature of germination, it is possible to adjust the quality of malt. Muñoz-Insa et al [191] have shown that there is a positive correlation between the germination temperature and the total phenolic content, and a negative one between higher degree of steeping and the total phenolic content. Recently, Wannemacher et al [12] investigated the impact of malt modification and hopping regime on the antioxidant potential of beer, and concluded that malt with higher raw protein content gives a beer with significantly higher antioxidant activity, determined using ORAC assay.…”
Section: Raw Materialsmentioning
confidence: 97%
“…With variations of parameters during the process of malting, such as degree of steeping, and time and temperature of germination, it is possible to adjust the quality of malt. Muñoz-Insa et al [191] have shown that there is a positive correlation between the germination temperature and the total phenolic content, and a negative one between higher degree of steeping and the total phenolic content. Recently, Wannemacher et al [12] investigated the impact of malt modification and hopping regime on the antioxidant potential of beer, and concluded that malt with higher raw protein content gives a beer with significantly higher antioxidant activity, determined using ORAC assay.…”
Section: Raw Materialsmentioning
confidence: 97%
“…Variations in malting regime (degree of steeping, germination temperature and germination time) are used as a tool to adjust malt quality parameters. The total polyphenol content in barley malt extracts was found to be positively influenced by germination temperature, but it was negatively influenced by higher degrees of steeping (Muñoz‐Insa, Gastl, & Becker, ). In their study of phenolic acid content in 68 barley genotypes and the corresponding malts, Cai et al.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, multiple regression analyses of the experimental data were done to calculate quadratic models. Different tests were used to validate the statistical models; these include the F‐value ( P < 0.05), the coefficient of determination ( R 2 > 80%), and the lack of fit ( P > 0.05) to assess the significance, the reliability, and the adequacy of the fitted model, respectively 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Different tests were used to validate the statistical models; these include the F-value (P < 0.05), the coefficient of determination (R 2 > 80%), and the lack of fit (P > 0.05) to assess the significance, the reliability, and the adequacy of the fitted model, respectively. 29,30 Quinoa and malt standard analyses The moisture of the samples was determined following MEBAK method R-200. 18.020 .…”
Section: Maltingmentioning
confidence: 99%